On their Own Skin: An Autobiographic Contribution to the Civil War. Composition of a Peculiar Narration - Rodríguez Suárez, María (Madrygal. Revista de Estudios Gallegos, 2015)
Through a collection of 16 stories, this article contains autobiographical anecdotes by a group of writers who survived the Spanish Civil War.